Teachers, emotions and school. Reflections in times of a pandemic (covid-19) - Buitrago, Rafael Enrique; Molina, Gloria Esperanza (Uptc, 2021)
This article is divided into several sections: Pandemic and education, which addresses some aspects that have occurred in educational contexts as a result of the covid-19 pandemic; Reflections about the school, where some tensions and distensions experienced by the school are raised; Fundamental Aspects of Emotions, dedicated to highlighting some characteristics of emotions and their relevance, with special emphasis placed on emotions in teachers and its impact on their well-being; and lastly, Final reflections, where people are invited to recognize themselves as emotional beings and strengthen empathy and their interpersonal bonds.